Assessing the Impact of social media on Youth's Entrepreneurship Development in Afghanistan - Barge Gul Khalili; Behnaz Rahimi; Mursal Akrami; Musaka Hejran; Hakimi, Musawer (International Journal of Integrated Science and Technology, 2024)
The study explores the obstacles to entrepreneurship that young Afghans face in the context of the nation's political and socioeconomic conditions. It looks at how important social media is to helping young people overcome these obstacles and become economically independent. Using a mixed-methods approach, it aims to comprehend the viewpoints, experiences, and variables influencing the use of social media among Afghan youth entrepreneurs by combining quantitative surveys and qualitative interviews with 160 participants. The majority of participants (75%) are male, and 62.5% have an economic background. Most of them are in the 25–30 age range. Targeted solutions are critically needed as financial and infrastructural limitations severely hinder entrepreneurial endeavours. Although social media can be used to expand a market and engage customers, perspectives on its effects are divided. The impact of digital literacy and prior entrepreneurial experience on self-assurance in leveraging social media as an entrepreneurial tactic is highlighted by regression analysis. These results highlight the need for customised interventions to improve digital literacy and bridge infrastructure gaps in order to fully utilise social media's potential to support Afghan youth's entrepreneurship. The present study enhances the conversation on young entrepreneurship and social media in developing countries by providing significant perspectives to policymakers, practitioners, and scholars who seek to support entrepreneurial ecosystems in Afghanistan and comparable settings.